Effects of water temperature and light intensity on the performance of gravity-driven membrane system. (February 2019) - Shao, Senlin; Shi, Danting; Li, Yueqi; Liu, Yang; Lu, Zhiying; Fang, Zheng; Liang, Heng
Abstract: The selection of favorable environmental conditions for gravity-driven membrane (GDM) systems is crucial to their widespread application. In this study, GDM systems operated under different light intensities (illuminance levels of 0, 200, and 3000 Lux) and water temperatures (10, 20, and 30 °C) were investigated for their performance and fouling layer characteristics. The results showed that indoor light (200 Lux) had limited effects on the performance of the GDM system. However, full daylight (3000 Lux) led to algal growth; these algae increased fouling resistance and deteriorated permeate water by releasing algogenic organic matter, although they could also enhance the heterogeneity of the biofouling layer by increasing the microbial activity. Water temperature rarely influenced the total organic matter removal. The fouling layers had different thicknesses and heterogeneity, but the same level of EPS; therefore, the hydraulic resistances of these fouling layer were almost the same at different water temperatures. These findings suggest that GDM system could be operated at low water temperature and indoor light conditions, and that strong light should be avoided during the operation of GDM systems. Highlights: Algae increased the heterogeneity of the biofouling layer. The biofouling layer of GDM system under different temperatures had identical resistances because of the same levels of EPS. GDM system could be operated at low water temperature and indoor light conditions.